Pola Asuh Orang Tua Sebagai Faktor Penentu Kualitas Pemenuhan Kebutuhan Dasar Personal Hygiene Anak Usia 6-12 Tahun - Umi Mardliyah; Anafrin Yugistyowati; Veriani Aprilia (Alma Ata University Press, 2014)
Health problems that often occur in children of primary school age (6-12 years) are diseases associated with personal hygiene of the children. This study aimed to determine the relationship of parenting pattern with quality fulﬁ llment of basic personal hygiene needs of children aged 6-12 years in SDN Asem Little Kulon Progo Yogyakarta. This analytic observational used cross-sectional study design. Sampling was determined with simple random sampling technique and obtained 86 students as respondents. Analysis using test Kendal Tau (τ) showed no association between parenting pattern with quality fulﬁ llment of basic personal hygiene needs of children aged 6-12 years in SDN Asem Little Kulon Progo Yogyakarta (p<0.05). The results provide input for health services to improve health education to the community, especially school-age children about personal hygiene associated with the prevention of disease through School Health Unit (UKS).